ANALISIS DU PONT SYSTEM UNTUK MENILAI KINERJA KEUANGAN PT ASTRA INTERNATIONAL TBK - El Ghifary, Alivia Putri; Irnawati, Jeni (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
This research aims to find out how the company's financial performance uses Du Pont System analysis which is measured by the Net Profit Margin (NPM), Total Assets Turnover (TATO), Return On Investment (ROI), Equity Multiplier (EM) and Return On Equity (ROE) ratios. The method used in this research is a quantitative method, the data used is secondary data in the form of annual financial reports at PT. Astra International Tbk for the 2013-2023 period which is listed on the Indonesia Stock Exchange. The data was analyzed using Du Pont System analysis by calculating formulas from the ratios used. Based on the research results, it can be concluded that the financial performance of PT. Astra International Tbk for the 2013-2023 period is in a bad position, the resulting positive value tends to fluctuate or be unstable every year. Based on standard industry ratios, the company is still below average, with an average NPM of 11.27% of 20%, TATO of 0.71 of 2 times, EM of 1.86 of 2 times, ROI of 8.05% of 30%, and ROE is 15.01% from 40%.